Default dan Cross Default dalam Perjanjian Kredit Bank - Johannes Ibrahim (Universitas Kristen Maranatha, 2002)
The formulating of covenant in bank credit agreement is under the authority of the bank as creditor. Covenants, which are formulating, from the financial and legal aspects are created in order to minimalize the risks in distributing credits. Two of the most important covenanrs are known as default and cross default covenants. Under these covenants, banks have the authority to terminate credit agreements and withdraw the rests of the loans from debitors. These covenants are created because as financial institutions funded by publics. banks need to keep their prudential banking policy in distributing their credits. However. in banking practice, the approprateness of these covenants are questioned since the freedom ofcontracts tends to be more beneficial for the banks than the debitors.Kata Kunci: Kredit, Perjanjian Kredit. Perjanjian Standar atau Baku. Klausula atau Covenant. Ingkar Janji (Default) dan Silang Ingkar Janji (Cross Default).